PEMBUNUHAN DI MAUMERE : Kewarganegaraan Pascapenjajahan - Gerry van Klinken (Institut Filsafat dan Teknologi Kreatif Ledalero, 2015)
This essay examines citizenship struggles in the small Indonesian town of Maumere during two decades of intensive state formation after decolonization in 1945. These struggles culminated in the bloody anticommunist purges of late 1965 and early 1966, which in this area mainly reflected “ethnic” tensions. They should not be seen merely as evidence of a deeply divided society, of elite factional fights over resources, or of state institutions that were too weak to exert effective control over society (though all those observations have some truth as well). Rather they were contentious efforts to establish new forms of public authority in the broad space between state and society. Novel informal institutions and rituals developed in the interstices between state and society. Christian Lund has called them “twilight institutions”. They all aimed to include ordinary people in public affairs. They were clientelistic, and their rivalry sometimes produced violence. Yet they were essentially about bringing ordinary people into a productive relationship with the new state; that is, they were about citizenship. The greatest irony of the “twilight institutions” is that they only became instruments of total exclusion after the central state began to assert itself decisively also in small provincial towns such as this. The history of “twilight institutions” continues to impress itself on actually existing forms of citizenship in the provinces today.